MEMBANGUN BRAND IMAGE SEBAGAI PENGELUARAN PRODUKTIF UNTUK BISNIS BERKELANJUTAN INDUSTRI KREATIF DI KOTA MALANG (Manajemen & Bisnis Jurnal, 2022)
Empowering the creative industry is one of the strategies of the Indonesian Ministry of Trade as an effort to strengthen the national economy. The creative industry, which is dominated by small and medium enterprises, is an industrial sector that is more resistant to various economic crises. As evidenced by various economic crises and the last one being the economic crisis due to the Covid-19 pandemic, the creative industry as part of small and medium enterprises has become an industry that is quick to adjust to the existing situation compared to large-scale industries. In general, the creative industry sector also has a significant economic contribution to the Indonesian economy which can create a positive business climate, strengthen the image and identity of the Indonesian nation. One of the efforts to increase product competitiveness is through brand image. Building a brand image cannot be done instantly, it is necessary to sacrifice resources so that the product has a special identity that will maintain the competitiveness of the product. Through case study qualitative research methods, this research aims to build a brand image in the creative economy industry as a form of investment that can maintain business continuity. The creative industry needs to position the brand as a valuable asset that can provide benefits in the future. Through in-depth interviews with creative industry players, the factors needed to build a brand image in helping business continuity in terms of increasing company sales are obtained. This research is expected to provide practical benefits for creative industry players by building their brand image so that they are able to compete and survive in business competition with large industrial products that already have brands